Rafael correa’s democratic revolution (2008)
This document aims at highlighting the political process in Ecuador from January 2006 and its alignment in the socalled XXI Century Socialism. Hence fore, the article is divided into four parts. Firstly, we explore Rafael Correa’s profile. That implies an analysis of his education, his professional career and his political movement Alianza País. Secondly, we will study his proposal for a new Constitution. At such aim, there will be a comparison between the current process and the previous one in 1998. Likewise, the clashes among public branches, legislative and executive, caused by the call to a new Constitution will be described. Thirdly, economic affairs will be treated based on the following concerns: re-negotiation of foreign debt, the South Bank project, management of natural resources and the state’s role in domestic economy. Finally, Ecuadorian foreign policy under Correa’s rule will be assessed, especially towards Colombia.